Do Elementary Science Methods Textbooks Promote Understanding of Shadows? - Lloyd H. Barrow (Intelektual Pustaka Media Utama, 2016)
Elementary science methods textbooks can be an important resource for future elementary teachers of science. Since shadows are a common topic in elementary school and Next Generation Science Standards (NGSS Lead States, 2013). A series of ten shadows concepts were formed into a learning progression by Wizman and Fortus (2007). For this research, ten science methods textbook were read and analyzed about how each of the shadow concepts were addressed. These methods textbooks focused on a limited number of shadow concepts. Consequently, as a future reference, they are very limited in addressing all ten shadow concepts.